2018
DOI: 10.1182/blood-2018-99-117545
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Khorana Score in Acute Myeloid Leukemia Patients: A Single Institution Experience

Abstract: Background: Although patients with acute myeloid leukemia (AML) were shown to have an increased risk of thrombosis, no thrombosis risk assessment scoring system has been developed for AML patients. The Khorana Risk Score (KRS), which has been widely used for thrombosis risk assessment in the clinical setting, was developed on the basis of solid tumor data and has not been validated among AML patients. This study aims to validate the use of the KRS as a thrombosis risk-scoring system among patients with AML. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…A recent study aimed to validate the Khorana score in AML. 19 The study showed that there was a higher incidence of thrombotic events in patients with higher Khorana score although the difference was not statistically significant and the performance of the score was suboptimal. The study suggested the need for developing a better thrombotic risk scoring system in AML.…”
Section: Discussionmentioning
confidence: 89%
“…A recent study aimed to validate the Khorana score in AML. 19 The study showed that there was a higher incidence of thrombotic events in patients with higher Khorana score although the difference was not statistically significant and the performance of the score was suboptimal. The study suggested the need for developing a better thrombotic risk scoring system in AML.…”
Section: Discussionmentioning
confidence: 89%
“…The Khorana score is also valid for use in hospitalized cancer patients [ 165 , 166 ]. Attempts to validate the Khorana score for specific subpopulations of cancer have been less successful, and in studies of lung cancer, hepatocellular carcinoma, acute myeloid leukemia, and lymphoid malignancies, the Khorana score did not adequately stratify or predict VTE events [ 167 , 168 , 169 , 170 ].…”
Section: Prevention: Acquired Riskmentioning
confidence: 99%
“…Thrombotic events are signi cant complications in malignant patients. Thrombosis risk is well de ned for patients with solid tumors, and Khorana score is well validated for these patients, however, the value of Khorana scoring system in predicting the thrombotic events risk of hematological malignant diseases remains to be evaluated [27][28].…”
Section: Discussionmentioning
confidence: 99%